MULTILINGUALISM IN EU LAW: HOW PROMULGATION AUTHENTICATES EQUALITY - FELICI, Annarita (Comparative Legilinguistics, 2017)
EU law currently applies to 27 countries and is available in 23 languages which all carry equal status. In practice, this is achieved though translation and by the work of the DGT (Directorate General Translation), which hosts the largest translation service in the world. But from a legal point of view, translation is institutionally ‘non-existent’ and EU languages are all equal and authentic. The issue has been given attention in the last two decades mostly from scholars, linguists and translators (Correia 2003, Kjær 1999, Koskinen 2000, Šarčević 2001, Tosi 2001, Wagner 2000), thus raising awareness on the paradox of translation and the lack of a proper EU language policy and legal culture. Focusing exclusively on legal texts and on the pragmatics of norms (Olivecrona 1994:[1962], von Wright 1963), I will argue that the equal authenticity of the EU language versions and the multilingual practice of the Union are less contradictory than they seem. The principle of equal authenticity applies only when texts are authenticated and published in the EU Official Journal. Before that, nothing prevents to regard them as translations or language versions.